The Facets of the Enlightenment Movement from a Libertarian Perspective:: Destroying the Myth of Rousseau as the ‘Compassionate Progressive’ - Reimers, Patrick (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
This paper pretends to explain the origins of the French Revolution, in particular in regards to its connection with the main proponents of the French Enlightenment. It argues that the Enlightenment movement was rather heterogeneous, shaped by many different thinkers with often incompatible views. The merits of Jean Jacques Rousseau in regards to conservation and education are described, while equivalently criticizing his rather collectivist ideas and his disputable views on women. It is argued that even if during the main period of the Enlightenment movement, liberal thinkers such as Montesquieu, Turgot, Lafayette and Condorcet had defined political theories based on individual freedom and competition, they were possibly “too far ahead of times” to significantly shape the French Revolution. Independently from the positive aspects of the Enlightenment movement, the actual French Revolution was often collectivist and nationalist and led to a violent phase – the ‘Reign of Terror’. Thus, this analysis allows us to understand the complexity and diversity of the Enlightenment movement and its relation to the actual French Revolution. Consequently, the revolution’s collectivist, nationalist and violent phase must be seen critically, also showing us that the implementation of democratic processes can bear risks, as the ‘majority rule’ can differ quite significantly to the concept of the ‘Rule of Law’.